Dari stres menuju pencerahan: manajemen stres dan burnout pemimpin rohani dalam pelayanan gereja - Setiabudi, Hengki Irawan; Hidayati, Ermin (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Church ministry is an activity to build the congregation towards spiritual maturity and experience with Christ in God's field. There are many service activities that the church has to serve fellow internal and external congregations. However, it cannot be denied that service which is supposed to provide feelings of gratitude, happiness, and a thirst for the meaning of serving others, is problematic because this service causes deep psychological fatigue (burnout). Burnout is a problem for many servants of God, especially spiritual leaders, which will cause a decrease in the quality of service, conflict, and have an impact on decreasing physical health as well as psychological and mental health. The aim of this research is to identify and analyze burnout management among especially church leaders, as well as having the ability to save from excessive stress towards enlightenment. The methodology used is library research accompanied by observations in service areas and also when interactive dialogue occurs during leadership-themed seminars. It was concluded that spiritual leaders, apart from having resilience based on the word of God, are also equipped with the science of emotional control and are especially intelligent in handling burnout with positive and constructive output.